Analisis Hasil Kerja PT. Bank Syariah Indonesia Dengan Pendekatan Sharia Maqashid Index Periode 2021-2023 - Puspitasari, Puspitasari; Dindadianti , Afif Ida; Ambarwati, Marfu'ah; Romdhoni , Arif; Rohmanudin, Rohmanudin (Journal of Economics and Business Research (JUEBIR), 2024)
This research aims to assess the performance of Bank Syariah Indonesia (BSI) using the Maqasid Syariah Index, which displays the performance of sharia banks based on three main metrics: Education (Tahdzib Al-Fard), Upholding Justice (Al-'Adl), and Public Interest (Al -Mashlahah). The main objective of Islamic sharia known as Maqasid Syariah is the source of these indications. The data sources are the financial reports and Annual Report of Bank Syariah Indonesia (BSI) from 2021 to 2023. The findings of this research provide an assessment of bank performance from a Maqasid Syariah perspective and can be a reference for bank management in developing action plans and guidelines that support the objectives of Islamic sharia